Food-based dietary guidelines for children and adolescents - Corrêa Rezende, Júlia Laura; de Medeiros Frazão Duarte, Maria Carolina; Melo, Giselle Rhaisa do Amaral e; Santos, Luana Caroline dos; Toral, Natacha (Frontiers in Public Health, 2022)
Objective This study aimed at reviewing food-based dietary guidelines (FBDGs) with content targeted at children and adolescents to present their main characteristics, thus enabling comparisons among countries. Design We conducted a search of the FBDGs available on the Food and Agriculture Organization (FAO) website, followed by a scoping review with a gray literature search to find FBDGs for children or adolescents non-listed on the FAO's website. Data extraction included the year of publication, language, and guidelines for the target group. Results From FAO website searches, 109 documents were found, and 17 of them could not be translated. The Scoping review search conducted in 5,190 articles, and none led to new guidelines, nor from the gray literature. Regarding the 92 FBDGs explored, 41 were specific for infants under 24 months old, children, and/or adolescents, and 51 were for the general population with information for the studied group. Twelve percent of the general FBDG and 35% of the specific ones have food icons. All of the guidelines were published after 2001. Latin America and the Caribbean were the regions that presented more specific FBDGs and the majority of countries with guidelines for fruits and vegetables. The information about fat (15 countries) and sugar (26 countries) consumption reduction is frequent. Reduction of sodium intake appears to be in the majority of guidelines after 2015. Food hygiene guidelines are recurrent in Latin American documents. NOVA classification was adopted in five countries and 21 countries approach recommendations for mealtimes. Both exclusive and continued breastfeeding guidance and healthy complementary feeding orientation are present in over 50% of the specific FBDG for infants and children under 24 months old. Conclusion Food-based dietary guidelines are diverse due to both the nutritional and political aspects of each region. Latin America stands out for its orientations for the studied group. Further studies should measure the possible impacts and comprehension of FBDGs.